Mental Simulation to Promote Exercise Intentions and Behaviors - Zhong, Weitan; Zhang, Guoli (Frontiers in Psychology, 2021)
Mental simulation, which employs specific patterns of imagery, can increase the intention to exercise as well as actual engagement in exercise. The present studies explored the effects of mental simulation on the intention to engage in exercise while regulating emotions. The first study confirmed that mental simulation did promote participants' intentions. The second found that video-primed mental simulation was a more effective method of exercise intention promotion than semantic-primed and image-primed mental simulation. In the third study, it was found that combining process-based and outcome-based mental simulations increased exercise intentions. Positive emotions mediated imagery ability and intention to exercise. The final study found that the mental simulation interventions most effective for exercise adherence were those that balanced the valence of process and outcome components, in such a way that a challenging process results in a positive outcome, or a smooth process results in a negative outcome. Each of these results have practical implications for exercise interventions that will be discussed.